2014
DOI: 10.11564/28-0-563
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between women’s socioeconomic status and empowerment in Burkina Faso: A focus on participation in decision-making and experience of domestic violence

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 25 publications
10
28
1
Order By: Relevance
“…This finding is in line with prior studies conducted in Ethiopia [22] and Egypt [37]. The possible reason might be due to the fact that employed women would have a control to their economy and therefore be more likely autonomous to decide on their own health care as compared with those who were unemployed [21,30,48,49]. However, a study from Pakistan had a contrasting finding [32] where secondary data analysis found that employed women had a lower odds of completion in the CoC as compared with unemployed women.…”
Section: Plos Onesupporting
confidence: 90%
“…This finding is in line with prior studies conducted in Ethiopia [22] and Egypt [37]. The possible reason might be due to the fact that employed women would have a control to their economy and therefore be more likely autonomous to decide on their own health care as compared with those who were unemployed [21,30,48,49]. However, a study from Pakistan had a contrasting finding [32] where secondary data analysis found that employed women had a lower odds of completion in the CoC as compared with unemployed women.…”
Section: Plos Onesupporting
confidence: 90%
“…These variables may be associated with greater access to and acceptability of modern contraceptives. Besides, previous research in Burkina Faso showed that greater socioeconomic position contribute to participation in household decisions which may include modern contraceptive use [42]. In fact, we found that household wealth, urban residency, and women's education were signi cantly and positively associated with opposition to domestic violence, in uence on household decisions, and freedom in seeking healthcare (Data not shown).…”
Section: Demographic Factorssupporting
confidence: 51%
“…Its effect on the dynamics of normative values, including gender-related values such as support for wife-beating, is changing over time (Norris and Inglehart 2002). The study found that in 2013, Protestant women were less likely than Catholic women to support wife-battery-a finding that has been observed elsewhere (for example in Burkina Faso: see Pambe et al 2014). The liberal gospel and doctrines professed by Protestants may explain this association.…”
Section: Religion and Support For Domestic Violencementioning
confidence: 71%